A new species of Stenodynerus (Hymenoptera, Vespidae, Eumeninae) from Pakistan - Qasim, Muhammad; Carpenter, James M.; Rafi, Muhammad Ather; Khan, Muhammad Rahim (Zootaxa, 2018)
A new species of Eumeninae, Stenodynerus punjabensis Qasim, Carpenter et Rafi, is described from Pakistan. A key to the Stenodynerus species of Pakistan is also included.